Ethnobotanical survey of medicinal wild plants in the Shouf Biosphere Reserve, Lebanon - Nizar Hani; Safaa Baydoun; Hatem Nasser; Tiziana Ulian; Nelly Arnold-Apostolides (BMC, 2022)
Abstract Background Medicinal plants and associated traditional knowledge play a vital role in supporting the livelihoods and resilience of indigenous communities. This ethnobotanical survey aims to identify medicinal plants used by the local communities of the Shouf Biosphere Reserve of Lebanon (SBR) and document the associated traditional knowledge. Methodology Focus groups and personal interviews with 133 informants of community members of 22 villages of SBR were performed during 2019-2022. Informants were selected using purposive sampling techniques based on their knowledge of medicinal plants and experience in traditional herbal medicine. Interviews were conducted using a semi-structured questionnaire through field visits. Results Informants were equally represented by females and males and had different demographic characteristics, and the main source of knowledge was ancestral. A total of 184 medicinal plant species belonging to 57 families were documented. The predominant families were Asteraceae (31 spp.), Lamiaceae (14 spp.), and Rosaceae (14 spp.). Leaves (23%) were the plant part most used. Decoction (45%) was the predominant preparation method, while internal (oral) use (47%) was the most frequent administration mean. Berberis libanotica, Dittrichia viscosa, and Daucus carota achieved the highest scores of frequency of citation (FC), relative frequency of citation (RFC), use value (UV), and fidelity level (FL). Furthermore, diseases and ailments of gastrointestinal tract were the category most treated. Conclusions Findings revealed a rich and diverse list of medicinal plants with associated traditional knowledge still actively used to treat a wide range of diseases. Future phytochemical and pharmacological studies are recommended to determine the efficacy and safety of plant species used. The management body of the SBR and all related authorities are invited to continue their conservation efforts to protect such rich biocultural heritage.